FDI and Domestic Investment: An Industry-Level View - Christian Arndt; Claudia M. Buch; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
Previous empirical work on the link between domestic and foreign investment provides mixed results which partly depend on the level of aggregation of the data. We argue that the aggregated home country implications of foreign direct investment (FDI) cannot be gauged using firm-level data. Aggregated data, in turn, miss channels through which domestic and foreign activities interact. Instead, industry-level data provide useful information on the link between domestic and foreign investment. We theoretically show that the effects of FDI on the domestic capital stock depend on the structure of industries and the relative importance of domestic and multinational firms. Our model allows distinguishing intra-sector competition from inter-sector linkage effects. We test the model using data on German FDI. Using panel cointegration methods, we find evidence for a positive long-run impact of FDI on the domestic capital stock and on the stock of inward FDI. Effects of FDI on the domestic capital stock are driven mainly by intrasector effects. For inward FDI, inter-sector linkages matter as well.
urn:nbn:de:bvb:19-epub-13340-8
Keywords: F21; F23; E22; 330; foreign direct investment; domestic capital stock